Study of spectrum sharing in integrated satellite-terrestrial system based on space-based interference cartography - Haitao WANG; Xiwen MAO; Chen ZHANG; Gengxin ZHANG (Tongxin xuebao)
To deal with the spectrum demand of new low earth orbit satellite (LEO) communication component and the aggregate interference generated by incumbent terrestrial component in future integrated satellite-terrestrial system, a novel space-borne spectrum-sensing (SS) and spectrum-database assisted spectrum-sharing scheme with interweave model for LEO cognitive system was proposed.Firstly, considering the adverse impact of the sparse distribution of LEO cognitive node (CN) on SS and interference cartography (IC), the concept of cognitive node position was put forward.Secondly, the spectrum-DB was built based on dual-threshold hybrid SS and IC with LEO cognitive system.Finally, a spectrum-sharing scheme with multi-state virtual network (MSVN) was designed, which could make the coexistence between terrestrial component and uplink of LEO component available.Simulation results indicate that the spectrum-database approach based on the proposed dual-threshold hybrid SS and IC can support the spectrum awareness of high reliability with relatively low-density LEO CN, and that the proposed cooperative access scheme based on spectrum-database and interweave model for LEO component can share spectrum with terrestrial one, but not significantly increase the end-to-end delay of LEO component.